Poverty Alleviation Through Women's Empowerment in the Desa Prima Program in Putat Village, Yogyakarta Special Region - Dian Safitri , Riska (Literacy: Journal of Education and Social Science, 2024)
This study explored the impact of the Desa Prima program in Kalurahan Putat, Yogyakarta Special Region, focusing on its role in empowering women and addressing poverty alleviation. Despite Indonesia's abundant natural resources, poverty remained a persistent issue, exacerbated by gender inequality in labor force participation. The program, introduced by the Ministry of Women's Empowerment and Child Protection, aimed to enhance women's economic productivity through collective business ventures such as coconut sponge cake production. A descriptive qualitative approach was employed, utilizing observations, semi-structured interviews, and documentation to evaluate the program's effectiveness. The findings indicated significant progress in women's economic and social conditions, including improved skills, economic independence, and community cohesion. The success of the program was attributed to structured support, leadership, and ongoing mentoring provided by DP3AP2A. Sociologically, the program demonstrated a shift towards greater gender equality and empowerment. The study concluded that while the program made positive strides, further development through product diversification and educational workshops was necessary for long-term sustainability and broader impact.